Novel multiscale control scheme for nonminimum-phase processes - Nandong, Jobrun; Zang, Zhuquan (American Chemical Society, 2013)
Nonminimum-phase (NMP) processes are frequently encountered in chemical plants, where the presence of right-half plane zeros and time-delays often impose limitation on the achievable control performance. In this paper, a new multi-scale control scheme for controlling NMP processes is introduced. The novelty of the proposed scheme is to decompose a given plant into a sum of basic factors/modes having distinct speeds of responses. Then, an individual sub-controller is specifically designed to control each of these plant modes. Finally, an overall multi-scale controller is synthesized by combining all the sub-controllers in such a way to enhance good cooperation among the different modes, which is an essential feature for good control performance and robustness. Extensive numerical studies demonstrate that, the proposed scheme can provide better nominal performance and performance robustness than some of the well-established control schemes.